In Vitro Anti-Inflammatory Potential of Buton Forest Honey through Nitric Oxide Inhibition in RAW 264.7 Macrophage Cells - Hariana Hariana; Wahyuni Wahyuni; Suryani Suryani; Ari Sartinah; Maulidyah Maulidyah; Agung Wibawa Mahatva Yodha; La Ode Muhammad Julian Purnama; Adryan Fristiohady (Pharmaceutical Reports, 2026)
Inflammation is a physiological defense response to injury, infection, or stress, mediated by various signaling molecules, including nitric oxide (NO). However, excessive NO production can contribute to tissue damage and the progression of inflammatory conditions. Honey, a natural product derived from floral nectar by bees, contains diverse bioactive compounds with potential pharmacological properties, including anti-inflammatory activity. Buton Regency, located in Southeast Sulawesi, is a major producer of forest honey, making it a promising source of bioactive honey with therapeutic potential. This study aimed to evaluate the in vitro anti-inflammatory activity of Buton forest honey by assessing its ability to inhibit NO production in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cells. The results demonstrated that Buton forest honey significantly suppressed NO production in a concentration-dependent manner. At concentrations of 500, 250, 125, 62.5, 31.25, 15.63, 7.81, and 3.91 mg/L, the percentages of inhibition were 94.69 ± 2.94%, 74.03 ± 2.43%, 67.40 ± 2.34%, 62.72 ± 3.09%, 51.80 ± 4.73%, 44.40 ± 4.73%, 19.06 ± 1.79%, and 12.82 ± 0.68%, respectively. Statistical analysis using one-way ANOVA followed by post hoc testing revealed significant differences among the tested concentrations (p 0.05). In conclusion, Buton forest honey exhibits significant anti-inflammatory activity by inhibiting NO production in macrophage cells, suggesting its potential as a natural source for the development of anti-inflammatory agents.